Michèle Roberts: Female Genius and the Theology of an English Novelist - Jasper, Alison (Text Matters: A Journal of Literature, Theory and Culture, 2011)
Since Simone de Beauvoir published The Second Sex in 1949, feminist analysis has tended to assume that the conditions of male normativity—reducing woman to the merely excluded "Other" of man—holds true in the experience of all women, not the least, women in the context of Christian praxis and theology. Beauvoir's powerful analysis—showing us how problematic it is to establish a position outside patriarchy's dominance of our conceptual fields—has helped to explain the resilience of sexism and forms of male violence that continue to diminish and destroy women's lives because they cannot be seen as questionable. It has also, I would argue, had the unintended consequence of intensifying the sense of limitation, so that it becomes problematic to account for the work and lives of effective, innovative and responsible women in these contexts. In order to address this problematic issue, I use the life and work of novelist Michèle Roberts, as a case study in female genius within an interdisciplinary field, in order to acknowledge the conditions that have limited a singular woman's literary and theological aspirations but also to claim that she is able to give voice to something creative of her own. The key concept of female genius within this project draws on Julia Kristeva's notion of being a subject without implicitly excluding embodiment and female desire as in normative male theology, or in notions of genius derived from Romanticism. Roberts' work as a writer qualifies her as female genius in so far as it challenges aspects of traditional Christianity, bringing to birth new relationships between theological themes and scriptural narratives without excluding her singular female desires and pleasures as a writer. This paper—as part of a more inclusive, historical survey of the work of women writers crossing the disciplinary boundaries between literature and Christian theology over the last several centuries also asks whether, in order to do proper justice to the real and proven limitations imposed on countless women in these fields across global and historical contexts, we need, at the same time, to reduce the Christian tradition to something that is always antithetical or for which women can take absolutely no credit or bear no responsibility.